- #1

- 40

- 0

So first I tried making an equation, and I wrote that the probability = P(rolling a 6)+P(rolling a 6 and not a 7 on the first roll and not a 9 on the first roll) + P(rolling a 6 and not a 7 on the first roll and not a 9 on the first roll and not a 7 on the second roll and not a 9 on the second roll) + ...

At this point I said let P(6) = x, P(not a 7) = y, P(not a 9) = z.

So I have P= x+xyz+xy^2z^2+... Factor out the x;

x(1+yz+y^2z^2+...)

Then I rewrote that as x*the sum of (y^i)(z^i) from i = 0 to infinity. Using an identity I got this to be x*[1/(1-yz)]. I subbed the numbers in to that, and got .5357 as an answer. Now, I don't know what the correct answer is but that seems wrong to me.

Can anyone help?

Thanks